Vis-á-Vis-á-Vis. The Three-dimensional and artistic view of a problem - Martínez-Mendoza, Ramón (Arte, Individuo y Sociedad, 2016)
ANPO (A Non-predefined Outcome) is an an art-making methodology that employs structuralist theory of language (Saussure, Lacan, Foucault) combined with Hegel’s dialectic and the theory of creation of space by Lefebvre to generate spaces of dialogue and conversation between community members and different stakeholders. These theories of language are used to find artistic ways of representing a topic that community members have previously chosen. The topic is approached in a way that allows a visual, aural, performative and gustative form. To achieve this, the methodology is split in four main steps: step 1 ‘This is not a chair’, Step 2 ‘The topic’, Step 3 ‘ Vis-á-vis-á-vis’ and step 4. ‘Dialectical representation’ where the defined topic is used to generate artistic representations.The step 1 is a warm up exercise informed by the Rene Magritte painting ‘This is not a Pipe’. This exercise aims to help the participants to see an object as something else than an object but as a consequence of social implications. Step 2, participants choose a random topic and vote for it. The artist/facilitator does not predetermine the topic, participants are the one who propose it and choose it. Step 3, will be analysed in this publication and finally step 4, the broken down topic is taken to be represented and analysed in different ways.